NÍVEL DE DIVERSIFICAÇÃO, QUALIDADE DE VIDA E SAÚDE E BEM-ESTAR FINANCEIRO DO INVESTIDOR: Uma Análise Regional (Gestão & Regionalidade, 2024)
This study aims to investigate the association between diversification and the variables of Financial Well-Being, quality of life and health, depression and investor anxiety (Southeast versus other regions). The sum of assets for diversification was used as proxies; the WHOQOL-100 scale for quality of life and health; and the Beck inventory for anxiety and depression; and as an indicator of financial well-being, the concept of the Credit Protection service was adopted. Through structural equation modeling and invariance testing, the results showed a positive relationship between diversification and financial well-being. Furthermore, financial well-being revealed a positive relationship with quality of life, on the other hand, it had a negative relationship with the anxiety and depression scales. Regarding the invariance tests, the results indicated that there are no significant differences between investors from the Southeast and investors from other regions.
Keywords: Asset Diversification. Quality of Life and Health. Financial Welfare.